Systemic colonization of clover (Trifolium repens) by Clostridium botulinum strain 2301 - Zeiller, Matthias; Rothballer, Michael; Iwobi, Azuka N.; Böhnel, Helge; Gessler, Frank; Hartmann, Anton; Schmid, Michael (Frontiers in Microbiology, 2015)
In recent years, cases of botulism in cattle and other farm animals and also in farmers increased dramatically. It was proposed, that these cases could be affiliated with the spreading of compost or other organic manures contaminated with Clostridium botulinum spores on farm land. Thus, soils and fodder plants and finally farm animals could be contaminated. Therefore, the colonization behavior and interaction of the botulinum neurotoxin (BoNT D) producing C. botulinum strain 2301 and the non-toxin producing Clostridium sporogenes strain 1739 were investigated on clover (Trifolium repens) in a field experiment as well as in phytochamber experiments applying axenic and additionally soil based systems under controlled conditions. Plants were harvested and divided into root and shoot parts for further DNA isolation and PCR assays; subsamples were fixed for fluorescence in situ hybridization (FISH) analysis in combination with confocal laser scanning microscopy (CLSM). To target C. botulinum and C. sporogenes, 16S rDNA directed primers were used and to specifically detect C. botulinum, BoNT D toxin genes targeted primers, using a multiplex PCR approach, were applied. Our results demonstrate an effective colonization of roots and shoots of clover by C. botulinum strain 2301 and C. sporogenes strain 1739. Detailed analysis of colonization behavior showed that C. botulinum can occur as individual cells, in cell clusters and in microcolonies within the rhizosphere, lateral roots and within the roots tissue of clover. In addition, we observed significant differences in the growth behavior of clover plants when inoculated with Clostridia spores, indicating a plant growth promoting effect. Inoculated plants showed an increased growth index (shoot size, wet and dry weight) and an enlarged root system, which suggests the involvement of phytohormonal effects induced by the systemic colonization of clover by C. botulinum strain 2301.